A New Computerized Test for Colour Deficiency - Murat IŞIK; Cemil ÖZ (International Journal of Applied Methods in Electronics and Computers, 2016)
10% percent of today's population suffers from colour vision deficiency. There are many tests to diagnose colour blindness in related literature. Ishihara pseudoisochromatic plates which have almost one-century background are being used widespread to diagnose if a subject is colour blind. In this study, a novel computerized test based on Ishihara tests has been designed. The new test has been applied on 12 individuals having colour deficiency and 50 individuals having normal colour vision. We have achieved 100% sensitivity and 100% specificity from the new test though Ishihara test results.